Comparison of rheumatological and gastrointestinal symptoms after infection with Campylobacter jejuni/coli and enterotoxigenic Escherichia coli. Issue 5 (1st May 2002) - Locht, H; Krogfelt, K A
Abstract : Objectives: To estimate the incidence of postinfectious joint complaints after Campylobacter jejuni/coli enteritis compared with enteritis caused by enterotoxigenic E coli (ETEC). To compare gastrointestinal symptoms, antibiotic treatment, and antibody levels among patients with and without joint symptoms. Method: Questionnaires were sent to 210 consecutive patients with Campylobacter infection and an equal number of patients with E coli (ETEC). Blood samples for anti- Campylobacter antibodies were collected after two weeks, three months, six months, and two years. Results: Twenty seven of 173 (16%) patients with Campylobacter and 10/177 (6%) with E coli (ETEC) reported joint symptoms (p=0.004). In the Campylobacter group duration of diarrhoea was a median of 13 days for patients with arthralgia and seven days for those without joint pain (p=0.0058). Patients with E coli had diarrhoea of longer duration than patients infected with Campylobacter (14 days v seven days; p=0.0005). E coli patients had fewer gastrointestinal symptoms than Campylobacter patients (p=0.0001). Fifty nine per cent of Campylobacter patients with joint pain had received antibiotic treatment because of enteritis compared with 26% with enteritis only (p=0.03). Campylobacter species and serotypes were equally distributed in both groups and there was no difference in anti- Campylobacter antibody levels between the groups. Conclusion: There was a significantly increased risk of developing joint symptoms after contracting Campylobacter infection compared with E coli. Campylobacter patients with joint pain had more severe gastrointestinal symptoms and longer duration of diarrhoea. Antibiotic treatment does not seem to prevent reactive joint symptoms. Levels of anti- Campylobacter antibodies were the same in both groups.